Feasibility of using time domain signals for structural health monitoring based on electromechanical impedance technique - Gao, Chenfeng (2017)
Consistently, avoiding any engineering structural failure is crucial for engineers in order to prevent economic loss and life-threat. Thus, structure health monitoring (SHM) becomes an essential tool to evaluate the damage and load impact on engineering structures. In the past several decades, many techniques for SHM have been developed, including electromechanical impedance (EMI) using piezoelectric transducers (PZTs). This technique is one such widely used SHM technique due to PZT’s superior actuation and sensing abilities. This results in health signatures in frequency domain for engineering structures under investigation. However, its relevance in the time domain was not studied. In this final year project (FYP), this EMI based SHM technique was executed in both frequency and time domains. However, mainly concentrated and validated the applicability in stress monitoring. Through the detection of various types of loading (axial/transverse) on structures made of different materials (aluminium/concrete) and thus more comprehensive understanding of PZT was professed. This FYP is expected to be very useful for SHM of civil, mechanical and aerospace engineering.